POULTRY FARMING SKILLS AS A CAREER TRANSITION FOR SPECIAL STUDENTS (MBPK) (Proceedings of International Conference on Special Education, 2025)
Despite the Malaysian government's target of a one percent employment rate for Persons with Disabilities (PWD) in the public sector, the current rate remains low at approximately 0.31 percent. Therefore, career transition programs are crucial in preparing Students with Special Educational Needs (SEN) for the workforce, post-school education, and independent living. To support this objective, a Poultry Farming Skills Project was conducted by SEN students from SMK Dato’ Abu Bakar Baginda, Sepang, Selangor, in collaboration with Universiti Putra Malaysia (UPM). The five-month study involved 24 SEN students and was carried out in two phases. The first phase focused on knowledge transfer through both theoretical and practical training at the Institute of Tropical Agriculture and Food Security. The second phase involved monitoring (both virtual and on-site) and reporting. The aim of this study was to provide students with a solid understanding and practical skills in poultry farming, enabling them to apply their knowledge in managing a poultry farm. Moreover, the study sought to nurture individuals who are capable, independent, and productive, thereby contributing to national economic development. The project also aimed to enhance the overall well-being of SEN students, while reflecting UPM’s commitment to sharing agricultural knowledge with underserved communities. Additionally, this initiative has supported teachers in guiding students' career pathways more effectively. Overall, the study has had a positive impact on strengthening the relationship between the university and the school, while equipping SEN students with relevant skills to improve their future employment prospects.